(untitled) (Research in Agriculture Livestock and Fisheries, 2024)
Astragalus membranaceus is a widely used Chinese medicine. To investigate the effect of Astragalus residue as a feed additive on growth performance, immune performance, and antioxidant capacity of growth finishing pigs, the daily gain, daily feed intake, immune performance, and antioxidant capacity of the experimental group and control group were measured. The results showed that the growth performance, immune performance, and antioxidant capacity of fattening pigs were improved by Astragalus residue, which indicated that Astragalus residue, as a feed additive, was safe and harmless, not only played a pharmacological role but also realized the recycling of resources, which was worthy of further study and popularization. Res. Agric. Livest. Fish. Vol. 11, No. 1, April 2024: 11-17